2008
DOI: 10.1302/0301-620x.90b11.20629
|View full text |Cite
|
Sign up to set email alerts
|

Ponseti casting

Abstract: We have modified the Ponseti casting technique by using a below-knee Softcast instead of an above-knee plaster of Paris cast. Treatment was initiated as soon as possible after birth and the Pirani score was recorded at each visit. Following the manipulation techniques of Ponseti, a below-knee Softcast was applied directly over a stockinette for a snug fit and particular attention was paid to creating a deep groove above the heel to prevent slippage. If necessary, a percutaneous Achilles tenotomy was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…15 In their study though, the authors did not correlate each cast material in regard to their efficacy. Similarly, Brewster et al, 8 using SRF, and Ng et al, 28 using fiberglass material, published their favorable clinical results.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…15 In their study though, the authors did not correlate each cast material in regard to their efficacy. Similarly, Brewster et al, 8 using SRF, and Ng et al, 28 using fiberglass material, published their favorable clinical results.…”
Section: Discussionmentioning
confidence: 89%
“…13 Alternative cast materials used in conjunction with the Ponseti method have been considered. 8, 13-15 Coss and Hennrikus 15 found that parents preferred semi-rigid fiberglass (SRF) over POP due to its ease of removal, durability, and performance.…”
Section: Introductionmentioning
confidence: 99%
“… 8 Semirigid fiberglass cast materials can be removed easily with unwinding alone in a few minutes. 10 On the other hand, the major disadvantage of fiberglass material is its high cost.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed different results compared to Pittner et al although we used approximately the same parameters such as complete time, different results could be secondary to the scoring system which was used and low number of the patients. Brewster et al 10 reported the results of clubfoot treatment with softcast. They used below knee soft casts and concluded that using below knee soft cast was comparable to those using above knee POP cast.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation